2021
DOI: 10.1016/j.jenvman.2020.111655
|View full text |Cite
|
Sign up to set email alerts
|

Using system dynamics to assess the complexity of rural toilet retrofitting: Case study in eastern China

Abstract: Rural toilet retrofitting (RTR) is a complex, dynamic system that is affected by many factors and the positive/negative feedback relationships between subsystems and variables. Traditional technologies and management methods face challenges in fundamentally describing and solving problems in RTR. To bridge this gap, this study utilizes system dynamics and causal loop diagrams to explain such problems based on data collected from the stakeholders of the RTR in Jiaozhou from 2018 to 2019. Specifically, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Some researchers pointed out that some towns and rural households are under heavy economic pressure ( 40 ). The lack of economic resources makes it difficult for the villagers to afford the cost of RTR and further maintenance and management, which creates vast barriers ( 41 ); further rollout of RTR may fail as soon as the government funding ends ( 42 ). Besides, this paper further emphasizes the critical role of human resources, which is rarely mentioned separately in related studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers pointed out that some towns and rural households are under heavy economic pressure ( 40 ). The lack of economic resources makes it difficult for the villagers to afford the cost of RTR and further maintenance and management, which creates vast barriers ( 41 ); further rollout of RTR may fail as soon as the government funding ends ( 42 ). Besides, this paper further emphasizes the critical role of human resources, which is rarely mentioned separately in related studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies believe that performance assessment is a necessary condition for RTR sustainability ( 43 ). All the performance assessments positively contribute to improving the efficiency of RTR ( 42 ). However, we found that the top-down assessment leads to a lack of effective communication and cooperation between policymakers and policy implementers, and the problem of “active on the top” and “inactive on the bottom” is prominent.…”
Section: Discussionmentioning
confidence: 99%
“…(iii) Rural latrine conversion faces an imperfect policy system, weak awareness of villagers in latrine construction, insufficient motivation for technological innovation, and lack of industry norms. To guarantee the smooth implementation of latrine conversion, measures such as increasing financial investment, strengthening publicity and education, and improving supervision, can be taken [46]. (2) Field 2: Rural sewage improvement research.…”
Section: Research Field and Key Contentmentioning
confidence: 99%
“…e microfluidic chip was initially saturated by the oil. e injection rate was set in the microinjection pump corresponding to the injection rate at the inlet of microfluidic chip [12,[50][51][52][53][54].…”
Section: Injection Experiments Schemementioning
confidence: 99%
“…e operation processes of each module were consistent with that of the water injection. After the flow in the microfluidic chip, we stabilized again, stopped the gas pump, removed the connecting pipeline between the modules, cleaned up the test table, and collected waste liquid [46,50,51,55].…”
Section: Injection Experiments Schemementioning
confidence: 99%